2021
DOI: 10.20452/pamw.16152
|View full text |Cite
|
Sign up to set email alerts
|

Airway remodeling assessed by quantitative computed tomography at various stages of asthma severity defined according to Global Initiative for Asthma report: a single-center study

Abstract: Asthma is one of the most common lung diseases, but it is still not fully understood. Airway remodeling in asthma refers to structural changes in airways. The relationship between the remodeling and asthma severity remains under investigation, and data on the intensity of airway remodeling by the Global Initiative for Asthma Report asthma severity classification is still scarce.With the use of advanced post-processing software and multi-slice computed tomography, it is possible to perform detailed measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Bronchial WT (BWT) and emphysema are more common in patients with severe asthma compared to mild asthma [125,[133][134][135]. However, other studies have not found a link with the severity of asthma [133,136,137]. WT% is a meaningful radiological marker in assessing lung function changes in asthma.…”
Section: Radiological Indicators For Assessing Severity Early Identif...mentioning
confidence: 99%
“…Bronchial WT (BWT) and emphysema are more common in patients with severe asthma compared to mild asthma [125,[133][134][135]. However, other studies have not found a link with the severity of asthma [133,136,137]. WT% is a meaningful radiological marker in assessing lung function changes in asthma.…”
Section: Radiological Indicators For Assessing Severity Early Identif...mentioning
confidence: 99%
“…Bronchial WT (BWT) and emphysema are more common in patients with severe asthma compared to those with mild asthma [125,[133][134][135]. However, other studies have not found a correlation with the severity of asthma [133,136,137]. WT% is a meaningful radiological marker in assessing lung function changes in asthma.…”
Section: Radiological Indicators For Assessing Severity Early Identif...mentioning
confidence: 99%